Factors linked to informal trade in Raez Patiño market from Huancayo - Pariona Ccanto, Esther (2020)
Objective: to analyze the main factors linked to informal trade in the Raez Patiño market, Huancayo, 2018. Method: the scientific and deductive method was used; the methodological approach was quantitative, basic type research, descriptive and explanatory level and non-experimental cross-sectional design; the sample consisted of 185 informal traders from the Raez Patiño market surroundings, from whom information was collected through a questionnaire. Conclusions: informal trade in various contexts of Latin America and Peru, as well as in Huancayo and specifically around the Raez Patiño market, is mainly linked to social and economic factors; between the social ones, there were identified: the low level of education, migration and unemployment; among the economic ones: little investment of economic capital, the desire of economic independence (in the case of women) and the need to collaborate in family income.   DOI: https://doi.org/10.31876/sl.v4i1.48